Usability Evaluation of a VibroTactile API for Web-Based Virtual Reality Experiences - Canelha, José (2021)
This paper presents the Vibrotactile Editor System for designing and programming Vibrotactile (VT) feedback for Virtual Reality (VR) experiences. We describe the system and a usability evaluation of the programmatic component for the A-Frame web-based VR framework through a set of programming tasks. The resolution of the tasks showed some difficulty in understanding the state of the component when developing without the VT hardware present. The results show a number of potential improvements that we discuss